2023
DOI: 10.3201/eid2902.221411
|View full text |Cite
|
Sign up to set email alerts
|

Orthopoxvirus Infections in Rodents, Nigeria, 2018–2019

Abstract: To investigate animal reservoirs of monkeypox virus in Nigeria, we sampled 240 rodents during 2018–2019. Molecular (real-time PCR) and serologic (IgM) evidence indicated orthopoxvirus infections, but presence of monkeypox virus was not confirmed. These results can be used to develop public health interventions to reduce human infection with orthopoxviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…and Rattus rattus. Though there had been recent human mpox cases in Nigeria at the time, another rodent in the study (Mus baoulei) was found to be PCR-positive for OPXV but not MPXV, suggesting the circulation of another poxvirus in the local rodent populations [61]. Following an investigation of human mpox in 2017 in the Republic of Congo (ROC), 22% of Emin's pouched rats (Cricetomys emini) were found to be seropositive [62].…”
Section: Monkeypox Virus In Wild Animalsmentioning
confidence: 92%
“…and Rattus rattus. Though there had been recent human mpox cases in Nigeria at the time, another rodent in the study (Mus baoulei) was found to be PCR-positive for OPXV but not MPXV, suggesting the circulation of another poxvirus in the local rodent populations [61]. Following an investigation of human mpox in 2017 in the Republic of Congo (ROC), 22% of Emin's pouched rats (Cricetomys emini) were found to be seropositive [62].…”
Section: Monkeypox Virus In Wild Animalsmentioning
confidence: 92%
“…The orthopoxviruses (OPXVs) are a genus of the Poxviridae's chordopoxvirus subfamily, including members that cause sickness in humans and other animals. The most well-known member of this genus, Variola virus (VARV), is a human-specific pathogen that caused smallpox, which was eliminated more than three decades ago after widespread immunization with the closely related vaccinia virus (VACV) [ 1 , 2 ]. The monkeypox virus (MPOX) is prevalent in several African nations.…”
Section: Introductionmentioning
confidence: 99%